Self-monitoring of blood glucose in noninsulin-treated type 2 diabetes: an overview - Kleefstra, Nanne (Dove Medical Press, 2009)
INTRODUCTION: The effectiveness of self-monitoring of blood glucose (SMBG) in noninsulin-treated patients with type 2 diabetes (T2DM) remains unclear. We aimed to review the trials investigating the effects of SMBG in this population. METHODS: Medline was searched until June 29, 2009. Randomized controlled trials (RCTs) of at least 12 weeks’ duration were included. Data on the following aspects were gathered: patient and study characteristics, effects on HbA(1c), quality of life and treatment satisfaction, and methodological quality. RESULTS: The search revealed 9 original RCTs. These studies were very heterogeneous, and 5 were classified as of high quality. The studies with the best methodology did not show an effect of SMBG on HbA(1c), the studies with the worst methodological quality did. Two out of the 4 studies that assessed quality of life showed a significant change in favor of the control group, 1 study showed a significant change in favor of SMBG. DISCUSSION AND CONCLUSION: We found an inverse relation between study quality and efficacy of SMBG. At this moment, there is no basis for general use of SMBG in noninsulin-treated T2DM patients.